Some remarks on an alternative approach for Boltzmann distribution of hydrogen atoms - Fabiano Nicola; Radenović Stojan (The University Thought: Publication in Natural Sciences, 2020)
We propose an alternative approach to Boltzmann distribution concerning the hydrogen atom and compare our results to previous formalism for some observables.